The Effect of Power and Motivation in Teacher Organizational Citizenship Behavior (OCB) at Madrasah Aliyah in Central Lombok District - Ridlo, M. Rasyid; Widodo, Suparno Eko; Elianasari, Elianasari (International Journal for Educational and Vocational Studies, 2020)
The objective of this research is to obtain information about the effect of power and trust on teachers organizational citizenship behavior (OCB). This research used survey method with path analysis. Sample in this research was used multi stage simple random sampling The conclusions of this research are: (1) There is a positive direct effect of power on organizational citizenship behavior (OCB). (2) There is a direct positive effect of Motivation  on teacher organizational citizenship behavior (OCB). (3) There is a positive direct effect of power on motivation.